2002
DOI: 10.1128/jvi.76.24.12981-12991.2002
|View full text |Cite
|
Sign up to set email alerts
|

Long-Distance Movement, Virulence, and RNA Silencing Suppression Controlled by a Single Protein in Hordei- and Potyviruses: Complementary Functions between Virus Families

Abstract: RNA silencing is a natural defense mechanism against genetic stress factors, including viruses. A mutant hordeivirus (Barley stripe mosaic virus [BSMV]) lacking the ␥b gene was confined to inoculated leaves in Nicotiana benthamiana, but systemic infection was observed in transgenic N. benthamiana expressing the potyviral silencing suppressor protein HCpro, suggesting that the ␥b protein may be a long-distance movement factor and have antisilencing activity. This was shown for ␥b proteins of both BSMV and Poa s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
118
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(123 citation statements)
references
References 79 publications
(136 reference statements)
3
118
0
2
Order By: Relevance
“…These experiments demonstrated that DGIs are a manifestation of RNA silencing, although why they occur in such islands is not known. Interestingly, the formation of DGIs against a chimeric hordeivirus was either reduced or inhibited in transgenic N. benthamiana plants expressing a VSR, the HC-Pro of potato virus A (Yelina et al, 2002); however the DGIs induced by infection with either TMV or CMV were not affected by the transgenic expression of PVY HC-Pro in tobacco (Shams-Bakhsh et al, 2007). Thus, DGI formation can be affected by VSR in some cases, as was the cycling of recovered and symptomatic tissues after infection by CMV (Fukuzawa et al, 2010), further linking these various phenomena involving plant-virus interactions.…”
Section: Dark Green Islandsmentioning
confidence: 99%
“…These experiments demonstrated that DGIs are a manifestation of RNA silencing, although why they occur in such islands is not known. Interestingly, the formation of DGIs against a chimeric hordeivirus was either reduced or inhibited in transgenic N. benthamiana plants expressing a VSR, the HC-Pro of potato virus A (Yelina et al, 2002); however the DGIs induced by infection with either TMV or CMV were not affected by the transgenic expression of PVY HC-Pro in tobacco (Shams-Bakhsh et al, 2007). Thus, DGI formation can be affected by VSR in some cases, as was the cycling of recovered and symptomatic tissues after infection by CMV (Fukuzawa et al, 2010), further linking these various phenomena involving plant-virus interactions.…”
Section: Dark Green Islandsmentioning
confidence: 99%
“…Localized recovery, or dark green islands (DGIs), may develop on chlorotic, virusinfected leaves. No viral nucleic acids and proteins are detected in DIGs, they are resistant to infection with the same virus (MOORE et al 2001), and siRNA specific to the virus accumulate in them (YELINA et al 2002). In tobacco plants, silencing of the gene NtRDRP1 that encodes an RNA-dependent RNA polymerase (a host factor required for RNA silencing), prevents the formation of DGIs after infection with TMV (XIE et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that co-evolution of viruses and their plant hosts has resulted in mechanisms that allow the host to inhibit, restrict or tolerate viral infections and the viruses to evade host defenses (YELINA et al 2002). The R gene-mediated resistance has evolved to inhibit infection with specific viruses, but viruses can overcome it due to mutations (amino acid substitutions) introduced to the viral AVR proteins during virus replication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the virus is encapsidated, it either moves from one cell to another using plasmodesmata, or infects other plants through vectors [2,18]. Though movement of viruses or nucleoprotein complex can also takes place using complexes of virus encoded movement protein (MP) [19], capsid protein (CP), HC-Pro [20] etc. In case of vector transmission, most of the plant viruses use insect vectors but do not replicate in insect vectors.…”
mentioning
confidence: 99%